Sports analytics analysis, visualisation, and decision making in sports performance - Jayal, Ambikesh; McRobert, Allistair; Oatley, Giles; O'Donoghue, Peter (Routledge studies in sports performance analysis, 2018)
As the analysis of big datasets in sports performance becomes a more entrenched part of the sporting landscape, so the value of sport scientists and analysts with formal training in data analytics grows. Sports Analytics: Analysis, Visualisation and Decision Making in Sports Performance provides the most authoritative and comprehensive guide to the use of analytics in sport and its application in sports performance, coaching, talent identification and sports medicine available.